DETERMINATION of MOTIVATION Muzakki PAYING ZAK at ZAKAT MANAGEMENT Institution (Case study on MSME owners) - Nurkholis Nurkholis; Prabowo Yudo Jayanto (Bina Nusantara University, 2020)
This study aims to test and analyze factors that influence the motivation of Muzakki to pay zakat through religiosity, understanding of zakat, level of income, environmental, accountability of zakat management agency and socialization of zakat management agency. The population in this research is all Muslim SMEs in Semarang, while 100 Muslim SME owners in Semarang that are randomly sampled. Data is collected using the questionnaires and analyzed using Structural Equation Modeling (SEM) and Partial Least Square (PLS) with Smart analysis tool PLS 3.0. The study shows that religiosity, understanding of zakat, income level, environment, and accountability of the zakat management agency has a positive and significant influence on the motivation of Muzakki to pay Zakaah. While socialization of zakat management zakat has no significant effect.